The Impact of Classroom Action Research (CAR) and Innovation on Teacher Professionalism: an Intervention of Competence - Yusron, Ali; Irawati, Junita; Teguh Setiawan Wibowo; Husen; Sudadi (SAFE-Network, 2023)
The objective of this study is to examine the influence of Classroom Action Research and Innovation on Incentives, with Competence serving as the mediating variable. The variables investigated in the research are Classroom Action Research, Innovation, Competence, and Teacher Professionalism. The data collection method employed was a survey conducted through the distribution of questionnaires. The analysis was conducted using Smart PLS 3.2.8 software, specifically utilizing Partial Least Squares (PLS) analysis. The research findings is a) Classroom Action Research has a positive and significant impact on teacher professionalism, b) Innovation has a positive and significant effect on teacher professionalism, c) Competence shows a positive and significant association with teacher professionalism, d) Classroom Action Research has a positive and significant effect on teacher professionalism through Competence, e) Innovation has a positive and significant effect on teacher professionalism through Competence. Based on these results, it is recommended that teachers at Mandailing Natal Regency Elementary School prioritize and enhance the influence of Classroom Action Research, Innovation, and Competence on Teacher Professionalism. This will contribute to the overall improvement of teacher professionalism in the school. By emphasizing the importance of Classroom Action Research and Innovation, teachers can enhance their professional development and contribute to the advancement of education quality.